2018
DOI: 10.1136/bmjopen-2017-017231
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of new-generation drug-eluting stents versus drug-coated balloon for in-stent restenosis: a meta-analysis of randomised controlled trials

Abstract: ObjectiveThe study sought to compare angiographic and clinical outcomes of new-generation drug-eluting stents (DES) versus drug-coated balloon (DCB) in patients with coronary in-stent restenosis (ISR).DesignMeta-analysis using data from randomised trial found by searches on PubMed, the Cochrane Library, ClinicalTrials.gov and websites of major cardiovascular congresses.SettingOnly randomised trials comparing DES with DCB were included.ParticipantsPatients with ISR in the included trials.InterventionsNew-genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The DCB technique has been successfully tested in ISR, where good clinical efficacy was demonstrated in most studies, but not in all. [15,16,3239] Current guidelines recommend the use of DCBs for patients with coronary ISR (class I, level of evidence A). [1,40] In addition, DCBs are now increasingly being seen as an attractive option for the treatment of SVD and bifurcation lesions.…”
Section: Drug-coated Balloons: the Technologymentioning
confidence: 99%
“…The DCB technique has been successfully tested in ISR, where good clinical efficacy was demonstrated in most studies, but not in all. [15,16,3239] Current guidelines recommend the use of DCBs for patients with coronary ISR (class I, level of evidence A). [1,40] In addition, DCBs are now increasingly being seen as an attractive option for the treatment of SVD and bifurcation lesions.…”
Section: Drug-coated Balloons: the Technologymentioning
confidence: 99%
“…A recent meta‐analysis of randomized controlled studies comparing both strategies suggested that interventions with new‐generation DES appear to be associated with significant reduction in per cent diameter stenosis and TLR at short‐term follow‐up, but had similar MACE, MI and cardiac death for patients with ISR compared with DCB …”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, the rate of in-stent restenosis 5 years after percutaneous coronary interventions has been reported to be nearly 5% for patients treated with drug-eluting stents and 10% for patients treated with bare metal stents. 5 For the VA, the incidence varies among different studies from 0% to more than 50% due to heterogeneity in study designs, types of stents, follow-up times, and evaluation methods. 9 The incidence of symptomatic severe in-stent restenosis is unknown, but, in such patients, it is very difficult to perform balloon dilation or a second stent placement in the area with restenosis, as the first stent sometimes protrudes to the lumen of the ScA for approximately 2-3 mm and forms a sharp angle with the ScA.…”
Section: Indicationsmentioning
confidence: 99%